The Types of Reinforcement Strategies Used by the Teacher in Motivating EFL Students at KG B Class in Bali Kiddy School - Arista, D.; Artini, L. P.; Ratminingsih, M. (Universitas Pendidikan Ganesha, 2018)
This study aimed at describing types and implementation of reinforcement strategies in motivating EFL students at KG B Class in Bali Kiddy School. This research was conducted in the second semester in the academic year of 2016/2017. The subjects of the research were a teacher and 22 students aged 5-7 years old. The data collected by two methods: observation and interview. It was found that Bali Kiddy used 5 types of reinforcement strategies, namely verbal reinforcement, gestural, contact, activity and token reinforcement. Each of these types consists of positive and negative reinforcement. For positive reinforcement Bali Kiddy used âgood, very good, very good job, good job, excellent, thats good, wow, strong child, smile, nodding head, thumbs up, clap hands, hugging the student, stroking the student back, rubbing their head, outdoor playing, writing student name on board, studying on floor with teacher, more time for playing, appointed as leader of a group, storytelling, break time at computer room, sticker and write comment on student bookâ. For the negative reinforcements were